Lung cancer survival among Florida male firefighters - Koru-Sengul, Tulay; Pinheiro, Paulo S.; Zhao, Wei; Hernandez, Monique N.; Hernandez, Diana R.; Maggioni, Alessandra; Kobetz, Erin N.; Caban-Martinez, Alberto J.; Lee, David J. (Frontiers in Oncology, 2023)
Introduction: Lung cancer is a leading cause of cancer incidence and death in the United States. Although most firefighters are fit and do not smoke, they are exposed to many known carcinogens on the job and chemical compounds by inhalation and dermal exposures during firefighting activities. Although there has been some progress and improvement in lung cancer screening, diagnosis and treatment, epidemiologic investigations on lung cancer survival for both career and volunteer firefighters are lacking. Methods: Data from the Florida Cancer Data System (1981-2014) was linked with firefighter certification records from the Florida State Fire Marshal’s Office to identify all patients of this occupational group; lung cancer cause-specific survival data was compared with other occupational groups using Cox regression models with occupation as main effect. Adjusted hazard ratios (aHR) and 95% confidence intervals (95%CI) were calculated. Results: Out of 210,541 male lung cancer cases diagnosed in Florida (1981-2014), there were 761 firefighters (604 career, 157 volunteer). Lung cancer death was slightly higher among volunteer (75.2%) than career-firefighters (74.0%), but lower than non-firefighters (80.0%). Survivals at 5-year were higher among firefighters (29.7%; career: 30.3%; volunteer: 27.4%) than non-firefighters (23.8%). In a multivariable model, compared to non-firefighters, firefighters have significantly higher cause-specific survival (aHR=0.84; 95%CI: 0.77-0.91); p<0.001). However, there were no significant survival differences between career and volunteer firefighters (1.14; 0.93-1.39; p=0.213). In separate multivariable model with firefighters as the comparator, other broad occupational groups had significantly lower cause-specific survival (white collar: 1.11 (1.02-1.21); blue collar: 1.15 (1.05-1.25); service: 1.13 (1.03-1.25); others/unknown: 1.21 (1.21-1.32); all p-values<0.02). Conclusion: Lung cancer survival is significantly higher among firefighters compared to non-firefighters but there was no significant difference between career and volunteer firefighters. Improved survival for firefighters might be due to a healthy worker effect, lower smoking rates relative to other worker groups, and possibly superior treatment compliance. Many firefighters are cross trained as EMT/paramedics and possess a level of medical knowledge that may favorably impact treatment engagement and better navigation of complex cancer care.